1994
DOI: 10.1007/bf01745103
|View full text |Cite
|
Sign up to set email alerts
|

Functional 5-HT receptor subtypes in the isolated canine common carotid artery

Abstract: The vascular responses to 5-hydroxytrypamine (5-HT), 5-carboxamidotryptamine (5-CT, a selective 5-HT1-like receptor agonist), alpha-methyl-5-HT (alpha-M-5-HT, a relatively selective 5-HT2 receptor agonist), noradrenaline (NA), and KCl were examined in isolated, cannulated, and perfused canine common carotid arterial preparations. They caused strong vasoconstrictions. The rank order of vasoconstrictive potency was 5-HT > alpha-M-5-HT > or = NA > 5-CT >> KCl. The 5-HT-induced vasoconstriction was significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Spiperone (1, 10 and 100 n M ) and methysergide (1, 10 and 100 n M ), both predominantly 5‐HT 2A receptor antagonists ( Feniuk et al ., 1985 ; Vhora & Chiba, 1994 ), decreased dose‐dependently the sensitivity to serotonin, but did not influence the maximal response reached. They acted as competitive, surmountable antagonists in sham and collared rings (Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…Spiperone (1, 10 and 100 n M ) and methysergide (1, 10 and 100 n M ), both predominantly 5‐HT 2A receptor antagonists ( Feniuk et al ., 1985 ; Vhora & Chiba, 1994 ), decreased dose‐dependently the sensitivity to serotonin, but did not influence the maximal response reached. They acted as competitive, surmountable antagonists in sham and collared rings (Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…Yet, the maximum response to 5‐HT was increased but did not reach statistical significance (Table 1). In the absence of the pre‐contractile agent KCl, the 5‐HT 2A antagonist spiperone (0.1 μ M ) ( Vhora & Chiba, 1994 ) induced a parallel rightward shift (123 fold) of the 5‐HT concentration response curves in sham rings without changing the maximum response or the Hill slope of the curve (Table 1, Figure 1). This is in agreement with the competitive and surmountable antagonism exerted by spiperone in the rabbit carotid artery ( Geerts et al ., 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…This pre‐stimulation will be mentioned as pre‐contractile status throughout the text. Subsequently, the two CRC's to 5‐HT (with and without pre‐contraction) were repeated in the presence of a 5‐HT 2A receptor antagonist, either spiperone (0.1 μ M ) ( Feniuk et al ., 1985 ; Vhora & Chiba, 1994 ) or ketanserin (0.1 μ M ) ( Conolan et al ., 1986 ; Van Nueten et al ., 1986 ), added 30 min prior to the organ bath. In each experiment one sham and one collared ring did not receive the antagonist or the pre‐contractile agent to allow for correction of time effects.…”
Section: Methodsmentioning
confidence: 99%
“…Transient intracellular Ca 2+ is an essential signaling system to regulate vascular constriction [8]. Serotoin selectively activates the 5-HT 2 receptor in vascular smooth muscle [9] that results in cytoplasmic Ca 2+ release, while a high concentration of potassium stimulates extracellular Ca 2+ influx through membrane voltage-dependent Ca 2+ channels. It was recently reported that WEB 2086, another PAF antagonist compound, effectively inhibited intracellular Ca 2+ elevation caused by PAF in smc [10].…”
Section: Discussionmentioning
confidence: 99%